Prevalence and Burden of Refractive Errors at National and Sub-national Levels in Iran. - Mohammadi, Seyed Farzad; Farzadfar, Farshad; Pour, Parinaz Mehdi; Ashrafi, Elham; Lashay, Alireza; Mohajer, Bahram; Lari, Mohsen Asadi (Journal of Ophthalmic & Vision Research, 2022)
Purpose: To estimate the prevalence, burden of refractive errors and their associated trend from 1990 to 2018 and geographic inequalities in Iran. Methods: Data regarding the epidemiology of refractive errors was extracted from three different sources: systematic review of published literature, data from visual school screening programs, and data from Iran's national health survey (NHS). The pool of all available data on refractive errors as well as demographic, location, and socioeconomic status covariates were fitted in spatio-temporal and Gaussian process regression models to predict the prevalence of refractive errors from the years 1990 to 2018 in 31 provinces grouped by age and sex in order to calculate years lived with disability (YLDs). Results: In 2018, the age-adjusted prevalence of refractive errors was 16.32% (95% uncertainty interval [UI]: 12.44-21.48%) in both sexes, 17.98% (95% UI: 13.74-23.61%) in women, and 14.66% (95% UI: 11.14-19.36%) in men. The prevalence of refractive errors reveals that it increases with age. Refractive errors contributed to 441.41 and 348.38 YLDs in men and women, respectively. The age-standardized prevalence growth was 31.30% in females and 24.32% in males from the years 1990 to 2018. Significant geographical heterogeneity was observed. The agestandardized YLDs rates of refractive errors represent an increasing trend of 28.9% increase from 1990 to 2018. Conclusion: Over 28 years, the prevalence of refractive errors increased significantly. Women tend to have higher rates of prevalence. The prevalence increased in older ages. Border provinces had the lowest prevalence. Agestandardized YLDs rates of refractive errors increased by about 30%.